Analisis Kemampuan Siswa Kelas VIII dalam Menyelesaikan Soal Literasi Numerasi - Dekriati Ate; Yulius Keremata Lede (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
In the 21st century, students are required to master the three skills, namely the quality of character, competence, and literacy. In order these skills to be achieved, the ability to think and reason is needed. One of literacy that closely related to the ability to thinks and reason is numeracy literacy. This research was conducted with the title: "Ability of Class VIII Junior High School Students in solving numeracy literacy questions". This research was conducted at St. Josef Freinadementz Junior High School, Kota District, Southwest Sumba Regency. The aim is to describe students' abilities in solving numeracy literacy problems. This research includes descriptive qualitative research, and it was carried out from July 2021 to September 2021 at SMP St. Josef Freinadementz, City District, Southwest Sumba Regency. The research subjects were 15 students of class VIII. Data were collected through numeracy literacy skills tests and interviews. The results showed that 73.3% of students were in the very poor category and 26.7% were in the less category, so it can be concluded that in general the students' ability in solving numeracy literacy questions is still low.